HARNESSING AI FOR ENHANCED LOGISTICS AND RESOURCE OPTIMIZATION IN DISASTER RESPONSE - Mragank Kumar Yadav (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
Artificial intelligence (AI) has become a game-changing tool that can help with disaster relief. By using AI-powered tools like predictive modeling, automated decision-making, and optimization algorithms, first responders can make logistics and resource allocation much more efficient and effective in the face of tragedies that are getting worse and happening more often. In this article, the different ways AI can be used in disaster response are discussed. These include dynamic resource allocation, automated resource deployment, optimized routing and logistics, predictive repair and management, cost optimization, and continuous improvement. The article analyzes real-life case studies and research results to demonstrate how AI can help solve common problems in disaster response - like lack of knowledge, limited resources, and trouble coordinating. Using AI in crisis response could save lives, cut down on damage to property, and make people more prepared for future disasters.